Components For An Educational Research. A Proposal - Armando Ulises Cerón Martínez; Luis Arturo Guerrero Azpeitia (European Scientific Journal, ESJ, 2016)
Scientific language differs from the language of common sense because it’s more precise about the phenomena to explain. A word or a term may have a different use or meaning in scientific language. In the case of educational research proper, accurate and explicit terms that support use is assumed. A first analysis of the detection of the use of theoretical concepts field, habitus, and capital proposed by the late French sociologist Pierre Bourdieu, in the papers presented under the Tenth National Congress of Educational Research (X CNIE) of the Mexican Council communicates here educational research (COMIE) held in Veracruz, Veracruz in 2009. In the first part is exposed the place that theoretical concepts have in educational research in general and in the second one an analysis of the papers discussed it is to arrive at a conclusion. This work is part of an investigation into the production processes of dispositions to educational research at Masters level postgraduate and research seminars notes in them.